1970
DOI: 10.1099/00221287-61-1-27
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Fixation by Sulphate-reducing Bacteria

Abstract: SUMMARYNitrogen fixation has been obained with strains of Desulfovibrio vulgaris and D . gigas, organisms hitherto believed to be incapable of using molecular nitrogen. Fixation has been demonstrated by increases in total nitrogen and by uptake of 15N2. Fixation of N, may be widespread in this genus of the sulphate-reducing bacteria. I N T R O D U C T I O NThe research reported here was begun as a result of Postgate's comment (19653) in a review that 'Most strains of Desulfovibrio do not fix nitrogen'. Enriche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

1972
1972
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(33 citation statements)
references
References 5 publications
0
32
0
Order By: Relevance
“…Phosphate input from weathering is an obvious candidate driver for periods of nitrogen fixation (therefore euxinia) during the Proterozoic, one which could conceivably have been enhanced (above the previous non-biologically enhanced rate) by colonization of the land surface 37 towards the end of the Neoproterozoic. In a similar speculative vein, the basic idea that sulphate-reducing bacteria spent an appreciable fraction of their evolutionary past in an environment experiencing bioavailable nitrogen stress is circumstantially supported by the observation that sulphate reducers are capable of facultative nitrogen fixation 33 . It is even conceivable that nitrogen fixation under euxinic conditions could produce a negative d 15 N signature 34 which future geochemical data may record, and which would work in the same direction as our semiquantitative isotopic predictions.…”
Section: Discussionmentioning
confidence: 99%
“…Phosphate input from weathering is an obvious candidate driver for periods of nitrogen fixation (therefore euxinia) during the Proterozoic, one which could conceivably have been enhanced (above the previous non-biologically enhanced rate) by colonization of the land surface 37 towards the end of the Neoproterozoic. In a similar speculative vein, the basic idea that sulphate-reducing bacteria spent an appreciable fraction of their evolutionary past in an environment experiencing bioavailable nitrogen stress is circumstantially supported by the observation that sulphate reducers are capable of facultative nitrogen fixation 33 . It is even conceivable that nitrogen fixation under euxinic conditions could produce a negative d 15 N signature 34 which future geochemical data may record, and which would work in the same direction as our semiquantitative isotopic predictions.…”
Section: Discussionmentioning
confidence: 99%
“…Sequences clustering with known organisms using iron and sulfur as electron acceptors, namely Pelobacter carbinolicus (Lovley et al, 1995) and the species Caldicellulosiruptor saccharolyticus, which hydrolyses a variety of polymeric carbohydrates (Rainey et al, 1994), were found in low (2%) abundance (at 46, 90, 412, and 1,108 m). Sequences closely related to sulfate-reducing bacteria of the genus Desulfovibrio, such as Desulfovibrio desulfuricans (Steenkamp and Peck, 1981;Lobo et al, 2007), Desulfovibrio vulgaris (Riederer-Henderson and Wilson, 1970;Muyzer and Stams, 2008), and Desulfovibrio salexigens (Postgate and Campbell, 1966;van Niel et al, 1996) were detected at all stations. Archaeal genes, which could potentially harbor diazotrophic methanogens, were not detected.…”
Section: Molecular Analysis Of the Nifh Genementioning
confidence: 90%
“…Only N 2 fixing prokaryotes (diazotrophs) have the capability to convert N 2 to bioavailable N, i.e., ammonium, and make it available for nondiazotrophic organisms (Ward and Bronk, 2001;Gruber, 2008). Diazotrophs can be detected using molecular tools such as the nifH gene, the key functional marker encoding a subunit of the nitrogenase reductase enzyme (Sisler and ZoBell, 1951;Riederer-Henderson and Wilson, 1970;Zehr and Turner, 2001).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sulfate-reducing bacteria can fix N and diazotrophy is widespead among mezophilic sulfur reducing bacteria (Riederer-Henderson and Wilson 1970;Postgate and Kent 1985;Welsh et al 1996b;Steppe and Paerl 2002). The abundance and activity of sulfur reducing bacteria is driven by anoxia, the presence of sulfates and high C availability.…”
Section: Introductionmentioning
confidence: 99%